Evaluasi Ketinggian Bendungan Plumbon Kabupaten Wonogiri terhadap Debit Desain Tahun 2024 - Aditya Eka Setiawan; Agus Hari Wahyudi; Cahyono Ikhsan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Indonesia has many dams that have been established since the Dutch Colonial era, including the Plumbon Dam located in Wonogiri Regency. During this time, many changes have occurred, including changes in flood discharge. The impact of climate change and land use change around the watershed has led to an increase in the frequency of extreme rainfall, which contributes to an increase in flood discharge. This study aims to evaluate the height of Plumbon Dam, assessing its safety against the new planned flood discharge. A 1000-year return period discharge and PMF analysis of Plumbon Dam was conducted for the year 2024. The calculation of rainfall R1000 and PMP using the Isohyet method, with the calculation of synthetic unit hygrograph using the HSS Nakayasu method. The calculation results obtained flood discharge Q1000 value of 73,33 m3/s and QPMF obtained at 107,75 m3/s. The required dam crest elevation was obtained, for Q1000 discharge + 227,43 m and QPMF + 226,96 m. The results of calculations using the 2024 design flood discharge are stated to experience overtopping of the 1000-year return period discharge because the flood water level exceeds the existing dam crest height of + 227 m and is safe against QPMF discharge.